Certain biochemical changes in uterine fluid during follicular and luteal phases of estrous cycle and certain reproductive disorders in buffaloes - RAJU, K G S; RAO, K S; REDDY, K C S (The Indian Journal of Animal Reproduction, 2007)
The uterine fluid obtained after flushing from genitalia of36 slaughtered buffaloes was collected seperately. Biochemical assay on the flushing revealed that total protein levels were significantly higher in luteal phase of the cycle, and,from genitalia showing mucometra as against those tracts having smooth ovaries or endometritis. No significant change in albumin levels during two phases of estrous cycle, as well as, in smooth ovaries and endometritis was seen, except that of tracts suggestive ofmucometra. In mucometra the level was higher. Globulin levels were significantly higher in luteal phase and mucometra condition. Albumin to globulin ratio was higher in conditions of smooth ovaries and endometritis. Alkaline phosphatase activity was significantly higher in follicular phase of estrous cycle. Cholesterol levels recorded were highest in follicular phased followed by mucometra and Iuteal phase of the cycle.